Midwifery Care in Third Trimester Pregnant Women With Low Back Pain Discomfort in Maternity Hospital: Asuhan Kebidanan Pada Ibu Hamil Trimester III Dengan Ketidaknyamanan Nyeri Punggung Bawah Di Rumah Sakit Bersalin - Khusnah, Siti Asmaul; Rusydiati, Tutik; Cholifah, Siti (Indonesian Journal of Innovation Studies, 2020)
Pregnant women are a natural process, the possibility of experiencing physical and psychological changes. Which can cause pregnant women to experience discomfort. Among the third trimester discomforts in pregnant women, low back pain is the most commonly reported and often occurs in 60%-90% of pregnant women. With the aim of knowing the description of low back pain during the third trimester of pregnancy at PMB Anang Arief. This article uses a descriptive method that aims to create an objective picture of the situation, from data collection by history taking, examination, data analysis and documentation. The results of anamnesis that pregnant women are currently 9 months old with low back pain, the results of the examination of the mother's general condition are good and no problems are found, so that they can be analyzed and given appropriate management such as how to overcome the discomfort of low back pain. From the data that has been collected, it can be concluded that the general condition of the mother and baby is in good condition with low back pain discomfort.